2007
DOI: 10.1128/jcm.01519-06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Clinical Manifestations of Viral Gastroenteritis in Hospitalized Pediatric Patients in Northern Taiwan

Abstract: By reverse transcription-PCR or PCR, among 257 children with nonbacterial acute gastroenteritis (AGE), rotavirus, norovirus, astrovirus, enteric adenovirus, and multiple viruses were identified in 78 (30.4%), 21 (8.2%), 7 (2.7%), 51 (19.8%), and 53 (20.6%) patients, respectively. Higher disease severity was found for AGE caused by multiple viruses and by rotavirus alone. The majority of rotaviruses isolated from 2004 to 2006 belonged to genotypes G1 (20.4%), G2 (16.5%), G3 (27.2%), and G9 (21.4%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
42
3
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 15 publications
13
42
3
2
Order By: Relevance
“…These clinical manifestations are more severe than those of other causes of viral gastroenteritis (27). In our study, vomiting was associated with rotavirus positivity (Table 4), which aligns with the findings of other studies (20,28).…”
Section: Discussionsupporting
confidence: 81%
“…These clinical manifestations are more severe than those of other causes of viral gastroenteritis (27). In our study, vomiting was associated with rotavirus positivity (Table 4), which aligns with the findings of other studies (20,28).…”
Section: Discussionsupporting
confidence: 81%
“…The literature concerning symptom severity in norovirus and rotavirus gastroenteritis is heterogeneous [42]. A number of previous studies found lower levels of disease severity in norovirus than in rotavirus gastroenteritis, and most of these were carried out in developed countries [7,[43][44][45][46][47]. In contrast, other studies found no significant differences between the severity of rotavirus and norovirus infections [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Hastalık 4-8 günde kendini sınırlar 21 . Chen ve arkadaşları hastanede yatış sürelerini ortalama rota virüslerde ve adenovirüslerde 5'er gün olarak saptamışlardır 22 . Bizim çalışmamızda hastanede yatış süresi 3-5 gün arasında değişmekteydi.…”
Section: Kaynaklarunclassified